What Leads to Online Financial Fraud Victimization Among Consumers: An Empirical Analysis - Mohammad Tahir Zainuddin; Wan Nur Fazni Wan Mohamad Nazarie; Natasya Aina Abdul Khadir (Global Academic Excellence (M) Sdn Bhd, 2026)
The widespread adoption of digital technologies has enhanced modern life but simultaneously fuelled a surge in online financial fraud, generating severe socio-economic repercussions. Fraud, defined as intentional deception for personal gain, now represents a global phenomenon that undermines trust in financial systems. In Malaysia, the National Scam Response Centre (NSRC) documented 33,234 scam cases in 2023 with losses amounting to RM1.34 billion. By 2024, reported cases increased to 35,368, resulting in losses of RM1.58 billion, while in the first quarter of 2025 alone, consumers lost RM573.7 million to various online scams. This study investigates the underlying factors leading to fraud victimization among Malaysian consumers. Employing a quantitative survey with 267 respondents analysed through SPSS, the research identifies four primary predictors: poor knowledge, low self-control, financial pressure, and bad/ risky routine activities. Findings provide valuable insights for policymakers and financial institutions in designing targeted interventions to reduce victimization and strengthen consumer resilience.